New results on low-mass dark matter from the CRESST-II experiment. Issue 4 (May 2016) - Petricca, F; Angloher, G; Bento, A; Bucci, C; Canonica, L; Defay, X; Erb, A; v Feilitzsch, F; Ferreiro Iachellini, N; Gorla, P; Gütlein, A; Hauff, D; et al.
Abstract: The CRESST-II experiment is searching for dark matter particles via their elastic scattering off nuclei in a target material. The CRESST target consists of scintillating CaW04 crystals which are operated as cryogenic calorimeters at millikelvin temperatures and read out by transition edge sensors. Each interaction in the CaW04 target crystal produces a phonon signal and also a light signal that is measured by a secondary cryogenic calorimeter. The low energy thresholds of these detectors, combined with the presence of light nuclei in the target material, allow to probe the low-mass region of the parameter space for spin-independent dark matter-nucleon scattering with high sensitivity. In this contribution results from a blind analysis of one detector module operated in the latest measurement campaign are presented. An unprecedented sensitivity for the light dark matter has been obtained with 52kg live days and a threshold of 307eV for nuclear recoils, extending the reach of direct dark matter searches to the sub-GeV/c 2 region.